Electrospun cellulose acetate fibers: Effect of solvent system on morphology and fiber diameter - Tungprapa, Santi; Puangparn, Tanarinthorn; Weerasombut, Monchawan; Jangchud, Ittipol; Fakum, Porntiva; Semongkhol, Somsak; Meechaisue, Chidchanok; Supaphol, Pitt (My University, 2007)
This paper reports an investigation of the effects of solvent system, solution concentration, and applied electrostatic field strength (EFS) on the morphological appearance and/or size of as-spun cellulose acetate (CA) products. The single-solvent systems were acetone, chloroform, N, N-dimethylformamide (DMF), dichloromethane (DCM), methanol (MeOH), formic acid, and pyridine. The mixed-solvent systems were acetone-DMAc, chloroform-MeOH, and DCM-MeOH. Chloroform, DMF, DCM, MeOH, formic acid, and pyridine were able to dissolve CA, forming clear solutions (at 5% w/v), but electrospinning of these solutions produced mainly discrete beads. In contrast, electrospinning of the solution of CA in acetone produced short and beaded fibers. At the same solution concentration of 5% (w/v) electrospinning of the CA solutions was improved by addition of MeOH to either chloroform or DCM. For all the solvent systems investigated smooth fibers were obtained from 16% (w/v) CA solutions in 1:1, 2:1, and 3:1 (v/v) acetone-DMAc, 14-20% (w/v) CA solutions in 2:1 (v/v) acetone-DMAc, and 8-12% (w/v) CA solutions in 4:1 (v/v) DCM-MeOH. For the as-spun fibers from CA solutions in acetone-DMAc the average diameter ranged between 0.14 and 0.37 μm whereas for the fibers from solutions in DCM-MeOH it ranged between 0.48 and 1.58 μm. After submersion in distilled water for 24 h the as-spun CA fibers swelled appreciably (i.e. from 620 to 1110%) but the physical integrity of the fibrous structure remained intact. © Springer Science+Business Media, Inc. 2007.
Keywords: Cellulose acetate; Electrospinning; Solvent; Ultrafine fibers